Diagnoza sytuacji kobiet na rynku pracy w Lubuskiem = Diagnosis of the position of women in the Lubuskie job market - Rutkowska, Monika (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Work gives women the chance of being active in professional and public life. Quite often women take up a job in order to enlarge the home budget. However, it is still more difficult for them to find a job, that is why the number of unemployed women is constantly growing.
Keywords: Lubuskie; rynek pracy; kobieta